Analisis Gaya Komunikasi Konten Edukasi Karir @vmuliana di Tiktok dan Persepsinya di Kalangan Mahasiswa KPI Universitas Ibn Khaldun Bogor - Hasya Septiawati; Ibdalsyah Munir; Nurman Hakim (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2026)
The challenge in this study lies in analyzing the communication style of career-related educational content on TikTok, as it relies on the audience's subjective interpretation. Furthermore, there are issues regarding the representativeness of the sample—comprising students from the Islamic Communication and Broadcasting (KPI) program at Ibn Khaldun University Bogor—as well as the potential for TikTok's algorithms to introduce bias and influence perceptions. The validity of these perceptions is also affected by the respondents' level of digital literacy. This study aims to describe the communication style of @vmuliana in career education content on TikTok and the perception of KPI UIKA Bogor students toward that communication style. Using a descriptive qualitative approach, data were collected through content observation of 10 @vmuliana videos published during October–December 2025 and in-depth interviews with four informants from semesters 2, 4, 6, and 8. Communication style was analyzed using Robert W. Norton's (1983) Communicator Style Measure (CSM), while perception was analyzed through three components: cognition, affection, and conation. The findings reveal that @vmuliana's communication style is dominated by seven CSM indicators—Friendly, Animated, Open, Impression-Leaving, Precise, Attentive, and Dramatic—while the Dominant and Contentious styles were absent. Students' perception was positive across all three levels simultaneously, with a pattern showing that the higher the semester, the greater the urgency for career information and the more concrete the actions taken.